Fracture and electric‐field‐induced crack growth behavior in NBT‐6BT relaxor ferroelectrics. Issue 5 (25th January 2021) - Shi, Xi; Kumar, Nitish; Jones, Jacob L.; Hoffman, Mark
Abstract: The fracture properties of 0.94(Na0.5 Bi0.5 )TiO3 ‐0.06BaTiO3 (NBT‐6BT) relaxor ferroelectrics were investigated using the Vickers indentation method and computation of crack tip opening displacement. It was found that an unpoled sample had a fracture toughness of around 1.35 MPa m 1/2 . In contrast, an electrically poled sample exhibited anisotropy with a lower fracture toughness perpendicular to the poling direction and a higher value in the parallel direction, as compared to the unpoled sample. Upon cyclic electrical loading (with applied electric field amplitudes between 0.73 E C and 1.4 E C ), the indented surface crack was found to propagate. In general, the crack grew rapidly during the initial cycles followed by crack arrest, and the principal driving force for crack growth was proposed to be residual stress around the indentation, as evidenced by the limited field dependence of crack growth. There was also a contribution from the electromechanical strain, which played a role at high cycles (>100 cycles) and high fields (>1.3 E C ). Evidence of a saturation threshold of crack propagation is an advantage for the electromechanical reliability of relaxor ferroelectrics in devices.